Sensory loss and its consequences for couples' psychosocial and relational wellbeing: an integrative review. (3rd April 2017) - Lehane, Christine M.; Dammeyer, Jesper; Elsass, Peter
ABSTRACT: Objectives: Previous research has shown that marital communication is key to couples' successful illness adjustment. However, little is known about couples' experiences of health conditions characterised by communication difficulties such as acquired hearing, vision, and dual-sensory loss. The aim of this review was to identify the effect of sensory loss, and associated communication difficulties, on couples' relational and psychosocial adjustment. Method: A systematic search was conducted to identify studies investigating the social, psychological, and relational impact of sensory loss on couples. Results: Twenty-four articles met the criteria for inclusion in the review. Significant heterogeneity in the measurements and design of the quantitative studies prevented statistical data synthesis. All but two studies reported some effect of sensory loss on couples' psychosocial or relational wellbeing. Higher levels of marital satisfaction were found to buffer against adverse psychological outcomes. Results of quantitative and qualitative studies were synthesised to form an integrative model illustrating the associations between sensory loss and couples' relational and psychosocial wellbeing. Conclusions: Although this review reports an association between sensory loss and couples' relational and psychosocial wellbeing, the results should be viewed with caution given that relatively few studies on couples' experiences of acquired sensory loss exist, and many have methodological limitations.